#ShameNot : campaign highlighting psychological trauma on victims of sexual assault in Singapore due to victim blaming mentally in society through real stories from real people - Thio, Jacqie Sijia (2018)
#ShameNot is a campaign that hopes to bring to light the psychological trauma that victim blaming may bring to victims of sexual assault, no matter whether is it a direct encounter or just voices in their head. With a collection of personal encounters from real people, these stories are recounted verbally and presented as an audio and visual experience to hopefully evoke empathy within its viewers. The experience continues with the viewers participating in a live data visualisation exercise which requires them to answer a few questions that will instigate them to think about their actions in their daily lives, and eventually prompts them to write a pledge to support the campaign, leaving with a token as a reminder of this issue.